Dampak pemberian Pupuk Organik Cair Kotoran Ternak terhadap Ketersediaan P dan Zn dan Serapannya oleh Tanaman Tomat (Solanum Lycopersicon L.) - Wachida Ayu Annisa; Setyo Budi Santoso; Wanti Midarti (Universitas Islam Malang, 2022)
The use of liquid organic fertilizer made from livestock manure is an attempt to provide tomato plants with P and Zn nutrients. This research aimed to assess the availability of P and Zn, the best growth, and yield of tomato plants using liquid organic fertilizer based on animal manure. A completely randomized design with a two-factor treatment was used to set up this study. The first aspect is the three different kinds of organic livestock-based fertilizers—chicken, goat, and cow dung. The second factor is the three different fertilizer concentrations, which are 5 ml/g (1), 10 ml/g (2), and 15 ml/g (3). A control was added as a point of comparison, and each treatment was performed three times overall for a total of 30 experimental units. After 7 days have elapsed after planting, liquid organic fertilizer is applied. The following parameters were measured: plant height, number of fruits, fruit weight, fruit sugar content, soil pH, soil accessible P, and total soil Zn. According to the findings, goat dung liquid fertilizer at a rate of 15 ml/g produced the greatest yield on tomato plant height. The treatment of 10 ml/g liquid organic fertilizer goat dung resulted in the highest Zn absorption in soil and tomato plants. The highest increase was seen with the 10 ml/g application of liquid organic fertilizer made from cow manure. In plant root P uptake (0.17 ppm).